Increasing Literacy and Numerization by Holding A 1st Primary Level Ranking Competition in Tambusai Village, Rumbio Jaya District, Kampar Regency - Munte, Mateo Samuel; Putri, Rahma Lia; Fadhila, Faiza; Rahmadanti, Salsabila; Wulandari, Aprilia; Hayati, Lulu; Annisa, Annisa; Simanjuntak, Jonatan Danuardi; Purnama, Irma Anggraini; Qasthalani, Azfa Duta (CV. Rayyan Dwi Bharata, 2023)
Literacy has a broad scope, not only talking about reading and writing letters, but also the ability to capture information with logical and critical thinking, ultimately being able to use it effectively to achieve certain goals. Reading is a process carried out to obtain a message and then convey it using written words. The reading literacy movement for students is an activity designed so that when students read, they are not only proficient at reading. However, students can also understand the content of the reading. The aim of this research is to improve students' reading skills. The method for implementing community service KKN activities is carried out through several stages, including the following: (1) Contacting cooperation partners with the Tambusai Village head to ask for permission to carry out KKN activities, (2) Discussing the work program that our group has prepared and linked it to the problem. what happens to children in the Tambusai Village environment, (3) Contacting elementary schools to carry out activities, (4) Measuring children's learning abilities by helping teachers carry out teaching activities, (5) Carrying out 1st ranking competition activities at Tambusai village elementary schools. The result of this service is children's reading ability by holding competitions that foster students' enthusiasm for reading and learning in order to win the competition.